DAUR ULANG DAN TANAM CERIA: EDUKASI PENGELOLAAN SAMPAH PLASTIK MENJADI POT TANAMAN DI SDN 13 UKS PAGI - Riska Ramdani; Arjun Arief Mustofa; Satriya Dzaki Pratama; Nazwa Haula Hidayat; Sahira Nadia Putri; Kiki Nurjanah; Herliani Ayu Nisa; Inge Anastasya (TRIDHARMADIMAS: Jurnal Pengabdian Kepada Masyarakat Jayakarta, 2026)
The community service activity titled "Daur Ulang dan Tanam Ceria" aims to increase students' understanding of waste management and support urban farming programs in schools. The main problem addressed is the low value of plastic waste in urban environments which is difficult to decompose. The method used is community education through socialization and training on making plant pots from used plastic bottles. The results showed that 60 students from grades 4 A and 4 B at SDN 13 UKS Pagi were able to transform plastic waste into aesthetic and functional planting media. A total of 100 plants were provided, where 60 seedlings were planted with students and 40 others were handed over to the school. The conclusion is that creative education through the reuse principle is effective in increasing students' enthusiasm regarding plastic waste issues.